Relevansi Kompetensi Lulusan SMK Khususnya Kompetensi Keahlian Teknik Gambar Bangunan dengan Kompetensi yang Dibutuhkan di Dunia Kerja - M Agphin Ramadhan; Tuti Iriani; Santoso Sri Handoyo (LPPM Universitas Negeri Jakarta, 2013)
The Objective of this study to determine the relevance of vocational high schools (SMK) graduates especially in drawing technique building (TGB) with competence is needed in the world of work. This research was conducted in the state vocational high schools (SMKN) in Jakarta who organized a program of TGB, they are SMKN 26, SMKN 35, SMKN 52, and SMKN 56, Jakarta, and in several companies of construction industry. The sample in this research a number of 40 people, they were graduated in 2010 and 2011. The research taken using a purposive sample techniques. There are three instrument used. First, instrument competence graduates who votes by The Chairman of the TGB programs. This instrument is basic competence of curriculum (KTSP) SMK of TGB. Second, instrument competence required in the work hosted by graduates SMK of TGB by self assessment. Third, instrument competence required in the work hosted by manager to judge ability graduates SMK of TGB. Based on the research can be concluded that graduates SMK of TGB is competent in drawing, using software, and softskill. But in terms of counting, ability graduates SMK of TGB still low.